Unrest in Turkey's Kurdish region: Challenges for Turkey and the EU - Heinz Kramer (Stiftung Wissenschaft und Politik (SWP), 2006)
In late March 2006, the Kurdish part of Turkey experienced its most violent clashes in a decade. Since then, the level of insecurity inside the country has risen, because it has become abundantly clear that there can be no question of any 'normalisation' of the Kurds' situation in Turkey. The Kurds themselves disagree on what constitutes the 'right' policy to conduct vis-à-vis the state, and Prime Minister Erdogan's government has no political concept for dealing with the problem. Moreover, the signals sent out to Turkey by the European Union vacillate between messages in line with the EU's anti-terrorism policy and appeals to respect human rights. It is high time for the EU and Turkey to engage in an intensive dialogue on the long-term objectives of their Kurdish policy and the best way of achieving these goals. (SWP-Comments / SWP)
Keywords: 320